2012
DOI: 10.1007/s10552-012-0070-3
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and survival in population-based patients with pancreatic cancer in the San Francisco Bay Area

Abstract: Background Obesity has been consistently associated with increased risk of pancreatic cancer incidence and mortality. However, studies of obesity and overall survival in patients with pancreatic cancer are notably lacking, especially in population-based studies. Methods Active and passive follow-up were used to determine vital status and survival for 510 pancreatic cancer patients diagnosed from 1995–1999 in a large population-based case-control study in the San Francisco Bay Area. Survival rates were comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
(31 reference statements)
1
14
0
1
Order By: Relevance
“…12,13,2131 For the purposes of data abstraction, all studies were cohort by design (with subjects being followed over time after exposure [obesity], for development of outcome [mortality]), although some studies inherently were reported as case-control studies. 12,24,25 Although 5 studies 12,21,2325 included a cohort of patients with established pancreatic cancer and reported the association between premorbid obesity and all-cause mortality, 8 studies were large cohorts of cancer-free participants at inception and followed them for development of pancreatic cancer-related mortality through record linkage with national death indices. The characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,2131 For the purposes of data abstraction, all studies were cohort by design (with subjects being followed over time after exposure [obesity], for development of outcome [mortality]), although some studies inherently were reported as case-control studies. 12,24,25 Although 5 studies 12,21,2325 included a cohort of patients with established pancreatic cancer and reported the association between premorbid obesity and all-cause mortality, 8 studies were large cohorts of cancer-free participants at inception and followed them for development of pancreatic cancer-related mortality through record linkage with national death indices. The characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1. Eleven studies were based in North America or Europe, 12,2125,2731 including 1 pooled study of 7 cohorts of black participants. 27 Two studies were conducted in the Asia-Pacific region, both pooled analysis of multiple individual cohorts (30 cohorts from the Asia-Pacific Cohort Studies Collaboration 26 and 16 cohorts from the Asia Cohort Consortium 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a previously conducted population-based study of PC in the San Francisco Bay Area, a significant proportion of patients died prior to study contact. 3,43,44 In the current study, recruitment of patients in the clinic helped minimize the potential for survival bias. Detailed information on potential confounding variables was gathered using validated questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…2 With active follow up of patients this rate drops to 2%. 3 This poor prognosis is partly attributable to metastatic disease at diagnosis. Even though genomic evidence suggests that PC cells take at least 5 years to develop metastatic capability, 4 more than 80% of patients have advanced and/or metastatic disease at the time of disease presentation, 5 at which point potentially curative surgery is not an option.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier population-based casecontrol study of PC in the San Francisco Bay Area(SFBA), the 5-year survival rate was 1.5%, with a 10-month median survival time using active follow-up methods [5,6].…”
Section: Introductionmentioning
confidence: 99%